An investigation of early childhood caries in the lower socio-economic areas surrounding Tygerberg Oral Health Centre in order to plan a community appropriate intervention strategy - Mohamed, Nadia (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2014.